Komparasi Metode Scoring System dan Profile Matching untuk Mengukur Kinerja Karyawan pada PT Wahana Rahardja - Darwis, Dedi (Jurnal Komputasi, 2019)
PT Wahana Rahardja is one of the companies in the field of material supply located in Bandarlampung. In this company, one of the management activities undertaken is to evaluate and evaluate employee performance so that based on the results of the assessment and evaluation, reward and punishment can be determined for employees. Currently, the way leaders in assessing employees are still based on perceptions and analysis so as not to produce an objective assessment. Therefore, a method is needed to measure employee performance so that the assessment can be more objective. In this study the method applied is scoring syetem and profile matching, the two methods will be compared and tested which is better and suitable to be applied in assessing employee performance at PT Wahana Rahardj. Employee performance appraisal is carried out using 3 aspects namely intelligence aspects, aspects of work attitudes and behavioral aspects and each aspect has sub-criteria. The results obtained from testing the Scoring System and Profile Matching methods show different results, the Profile Matching method is the method that will be recommended as the most appropriate method in evaluating employee performance because it can provide more objective results.